The role of firm characteristics in voluntary disclosure of IC information and its importance for high-techcompanies - Rep, Ana (Array, 2019)
The purpose of this paper is to analyse whether the extent and quality of voluntarily disclosed information regarding intellectual capital (IC) are correlated with certain characteristics of a company. IC is very important for IT companies. Therefore, financial and non-financial statements of 32 high-tech companies were investigated using the content analysis method. To test the influence of firm characteristics on the intellectual capital disclosure index (ICDI), the regression model was used. The size of the firm was the only independent variable that has had a statistically significant influence on the ICDI. The auditor type, as well as financial ratios, have not shown a statistically significant influence on the extent and quality of IC disclosures. This study reflects the state regarding the voluntary IC disclosures in Croatia and therefore the study may be a roadmap for further research and, more importantly, might promote awareness of the importance of transparent reporting.